Expression of CSTF2 in oral squamous cell carcinoma and its relationship with immune infiltration and poor prognosis - Aierken, Zumulaiti; Muhetaer, Muertiza; Lei, Zhang; Abudourousuli, Ainiwaerjiang (Frontiers in Oral Health, 2025)
BackgroundOral squamous cell carcinoma (OSCC) is a prevalent and devastating malignancy of the oral cavity that profoundly affects patient survival and quality of life (QOL). Cleavage Stimulation Factor Subunit 2 (CSTF2) is known to influence tumor development across multiple cancer types. However, its specific association with patient prognosis and immune cell infiltration in OSCC remains insufficiently understood.MethodsTo assess the expression levels and prognostic implications of CSTF2 in OSCC, comprehensive data were acquired from The Cancer Genome Atlas (TCGA) and subsequently normalized. Immunohistochemical staining of tissue microarrays was performed to analyze CSTF2 expression in the OSCC samples. Differences in CSTF2 expression between OSCC and adjacent non-cancerous samples were evaluated using the Wilcoxon rank-sum test. Functional enrichment analyses have been performed to identify biological pathways and functions associated with CSTF2. The relationship between the infiltration of various immune cells and CSTF2 expression levels was assessed using single-sample gene set enrichment analysis (ssGSEA). Ultimately, the prognostic significance of CSTF2 was evaluated through Kaplan–Meier survival analysis, in conjunction with univariate and multivariate Cox regression analyses, as well as receiver operating characteristic (ROC) curves.ResultsHigh CSTF2 expression was observed in OSCC and associated with unfavorable clinicopathological variables, including histological grade and lymphnode neck dissection. Functional enrichment analysis indicated that CSTF2 plays a role in epidermal development and differentiation, immunoglobulin complexes, peptidases and endopeptidase inhibitor activity, and cytochrome P450 metabolic processes. Additionally, the overexpression of CSTF2 exhibited a negative correlation with the infiltration of immature dendritic cells (iDCs), cytotoxic cells, and plasmacytoid dendritic cells (pDCs). Notably, elevated CSTF2 expression is significantly associated with reduced patient outcomes.ConclusionElevated CSTF2 expression in OSCC is associated with poor prognostic outcomes, highlighting its capacity to function as an innovative prognostic biomarker and a target for therapeutic interventions.